HUBUNGAN POLA MENSTRUASI DAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI SMA NEGERI 2 TEMBILAHAN - SARI, MIA RITA (JURNAL KESEHATAN MERCUSUAR, 2020)
The high prevalence of anemia among teenagers if it is not be handled properly, it will continue into adulthood and contribute greatly to maternal and infant mortality. Preliminary study was conducted in Senior High School Number 2 Tembilahan were 10 respondents on the result of hemoglobin check, 4 respondents did not have anemia and 6 respondents experienced anemia. The purpose of this study was to determine the relationship of menstrual pattern and nutritional status with the incidence of adolescent anemia in Senior High School Number 2 Tembilahan. This type of research is analytic quantitative with cross sectional design. The sampling technique is simple random sampling . The population is class XI and XII students of Senior High School Tembilahan with the number 146 students and number of samples were 99 respondents. Data werw collected through a questionnaire and examination of hemoglobin levels and then processed using univariate and bivariate analysis with chi square test. The research result was obtained most of respondents aged 17 years old as many 48,5%, normal menstrual pattern is as many 63,6%, abnormal nutritional status is as many 50,5%, there are no anemia is as many 57,6%, there is relationship between menstrual pattern and between nutritional status with the incidence of anemia with value p value = 0,000. It is expected that the school will continue to collaborate with health workers of UPT Public Health Centre of Gajah Mada in giving KIE to all students.